Antimicrobial and antioxidative activities in the bark extracts of Sonneratia caseolaris, a mangrove plant - Simlai, Aritra (EXCLI J, 2014)
The present study deals with the phytochemical contents, antimicrobial and antioxidative activities of bark tissue of Sonneratia caseolaris, a mangrove plant from Sundarban estuary, India. Phytochemical analyses revealed the presence of high amounts of phenolics, flavonoids, tannins, alkaloids and saponins. Antimicrobial efficacies of various extracts of S. caseolaris were assessed by disc diffusion method against two Gram-positive (Bacillus subtilis and Bacillus coagulans), two Gram-negative (Escherichia coli and Proteus vulgaris) bacteria and one fungus (Saccharomyces cerevisiae). The methanolic extract among others showed significant minimum inhibitory concentration (MIC) values. The antioxidant activity as indicated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity of the bark tissue extract from the species was found to be quite appreciable. The extracts were found to retain their antimicrobial activities despite pH and thermal treatments, thus indicating the stability of their activity even at extreme conditions. The antioxidant activity was also found to be considerably stable after thermal treatments. The components of the tissue extracts were subjected to separation using thin layer chromatography (TLC). The constituents with antimicrobial and antioxidative properties were identified using TLC-bioautography by agar-overlay and DPPH spraying methods respectively. A number of bioactive constituents with antimicrobial and radical scavenging properties were observed on the developed bioautography plate. The fractions with antimicrobial properties were isolated from the reference TLC plates and subjected to gas chromatography-mass spectrometry (GC-MS) analysis for partial characterization and identification of the metabolites that might be responsible for the activities. The study suggests Sonneratia caseolaris bark as a potential source of bioactive compounds with stable antimicrobial and antioxidative properties and can be used as natural antimicrobial/antioxidative agents in clinical, pharmaceutical and food processing industries.